Customer Experiences, Expectations and Satisfaction Level Towards Services Provided by Amazon - Goel, Pragya; Verma, Priyanka; Al Mutairi, Qoot; Bhardwaj, Rashi; Tyagi, Sahil (AIBPM Publisher, 2020)
Customer loyalty is considered as one of the most over used phrases in business today. For fulfilling these objectives, the descriptive research design has been used. The data from the multiple respondents have been collected. The survey involved gathering a wide information about the company, its products, customer satisfaction and the impact of various competitive firms on the company. Shoppers can easily visit the web site and shop just sitting in form of computer. Ability of the Internet contains wide range of collecting information, supplying a service or purchasing a product Amazon should work towards them so that it can increases its customers and finally profit.